2014
DOI: 10.1371/journal.pone.0108837
|View full text |Cite
|
Sign up to set email alerts
|

To Be or Want to Be: Disentangling the Role of Actual versus Ideal Self in Implicit Self-Esteem

Abstract: A growing body of work suggests that both depressed and non-depressed individuals display implicit positivity towards the self. In the current study, we examined whether this positivity can be underpinned by two qualitatively distinct propositions related to actual (‘I am good’) or ideal (‘I want to be good’) self-esteem. Dysphoric and non-dysphoric participants completed a self-esteem Implicit Association Test (IAT) as well an Implicit Relational Assessment Procedure (IRAP) targeting their actual self-esteem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 32 publications
2
54
1
7
Order By: Relevance
“…Perhaps the lack of differences between bipolar patients, unipolar patients and healthy controls means that implicit measures might not capture actual selfesteem but rather an ideal self (Remue et al 2013(Remue et al , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the lack of differences between bipolar patients, unipolar patients and healthy controls means that implicit measures might not capture actual selfesteem but rather an ideal self (Remue et al 2013(Remue et al , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, alternative implicit measurement procedures have recently been developed that operate in such a way that they do not depend on introspective access. In two recent studies using such an implicit measure, which enables the differentiation of ideal self and NEUROGNITIVE FRAMEWORK REGULATION EXPECTATION 22 actual self-esteem, it was demonstrated that dysphoric individuals have higher ideal selfesteem, and lower actual self-esteem compared to healthy participants (Remue, De Houwer, Barnes-Holmes, Vanderhasselt & De Raedt, 2013;Remue, Hughes, De Houwer & De Raedt, 2014).…”
Section: The Role Of Ideal Self-esteemmentioning
confidence: 99%
“…The crucial test would be to investigate whether the combinations we propose would be related to anticipation and proactive control, and the ability to deal with stressors. Although there are excellent measures to index ideal and actual self-esteem (both implicit and explicit, see Remue et al, 2014), future research should be focused on the development of procedures to assess the dimensions of expectancy/acceptance tendency. We have now developed a questionnaire to measure each of the combinations of expectancy and the tendency to accept during anticipation.…”
Section: Future Researchmentioning
confidence: 99%
“…Although many researchers take the position that human cognition is carved into two conceptually distinct mental systems (i.e., associative linking vs. propositional reasoning) that function under different operating conditions (i.e., automatic vs. controlled) (e.g., Gawronski & Bodenhausen, ), findings from the IRAP and other recently developed indirect procedures (e.g., De Houwer, Heider, Spruyt, Roets, & Hughes, ) offer another possibility: that humans can automatically relate stimuli in a wide number of ways and that the manner in which stimuli are related matters. Indeed, several researchers have found that relating the same stimuli in different ways (e.g., “I am good” vs. “I want to be good”; “I want unhealthy foods” vs. “Unhealthy foods make me hungry”) can lead to very different outcomes on the IRAP—outcomes that are often absent from self‐report procedures, which predict future behavior and differentiate between known groups (e.g., Carpenter, Martinez, Vadhan, Barnes‐Holmes, & Nunes, ; McKenna, Hughes, Barnes‐Holmes, Yoder, & O'Shea, in press; Remue, Hughes, De Houwer, & De Raedt, ; Rönspies et al, ). In this sense, the IRAP effect may represent one measure of implicit propositional knowledge (i.e., it captures the activation of propositions concerning how stimuli are related to one another under certain conditions of automaticity; for a more detailed treatment of this topic, see Hughes, Barnes‐Holmes, & De Houwer, ; De Houwer, 2014; De Houwer et al, ).…”
Section: The Implicit Relational Assessment Proceduresmentioning
confidence: 99%